Ground reaction forces, kinematics, and muscle activations during the windmill softball pitch - Oliver, G. D.; Plummer, H. (Journal of Sports Sciences, 2011)
The aims of the present study were to examine quantitatively ground reaction forces, kinematics, and muscle activations during the windmill softball pitch, and to determine relationships between knee valgus and muscle activations, ball velocity and muscle activation as well as ball velocity and ground reaction forces. It was hypothesized that there would be an inverse relationship between degree of knee valgus and muscle activation, a direct relationship between ground reaction forces and ball velocity, and non-stride leg muscle activations and ball velocity. Ten female windmill softball pitchers (age 17.6 ± 3.47 years, stature 1.67 ± 0.07 m, weight 67.4 ± 12.2 kg) participated. Dependent variables were ball velocity, surface electromyographic (sEMG), kinematic, and kinetic data while the participant was the independent variable. Stride foot contact reported peak vertical forces of 179% body weight. There were positive relationships between ball velocity and ground reaction force (r = 0.758, n = 10, P = 0.029) as well as ball velocity and non-stride leg gluteus maximus (r = 0.851, n = 10, P = 0.007) and medius (r = 0.760, n = 10, P = 0.029) muscle activity, while there was no notable relationship between knee valgus and muscle activation. As the windmill softball pitcher increased ball velocity, her vertical ground reaction forces also increased. Proper conditioning of the lumbopelvic-hip complex, including the gluteals, is essential for injury prevention. From the data presented, it is evident that bilateral strength and conditioning of the gluteal muscle group is salient in the windmill softball pitch as an attempt to decrease incidence of injury.